Biochemical evidence for a fifth cultigen within the genus Phaseolus - Debouck, Daniel G.; Schmit, Véronique; Libreros, Dimary; Ramírez, Hernando (1990)
A geographic frequency distribution of seed protein patterns of 306 individuals belonging to Phaseolus polyanthus is presented. Plant material covered the range of distribution of P. polyanthus from Veracruz, Mexico to Cajamarca, Peru. (CIAT)